Diseño de una estrategia pedagógica para disminuir la relación de la prevalencia de las infecciones respiratorias agudas y la contaminación ambiental - María Fernanda González-Vargas; María Eufemia Freire-Tigreros; Audin Aloiso Gamboa-Suárez (Mundo Fesc)
This article aims to design a pedagogical strategy based on the relationship between the prevalence of acute respiratory infections and air pollution in the municipality of La Cumbre. Correlational and descriptive research was used with two variables: air quality and acute respiratory infection diseases, followed by a quantitative and qualitative methodology with data collection and analysis through the use of two instruments: a citizen perception survey and an interview with a health professional. This methodology provided tools for collecting data on the frequency of medical consultations for non-COVID Acute Respiratory Infections during 2020 at the Santa Margarita Hospital located in the municipality of La Cumbre and background information on the air quality level indicator reported by The Weather Channel and environmental management. The results show a significant relationship caused by the population's poor habits and the need for an ongoing prevention program.